Pelatihan Transformasi Digital Arsip di Desa Darmaji Menggunakan Google Drive - Apriana Irawati; Sofiansyah Fadli; Sunardi Sunardi; Muhammad Masjun Efendi; Edi Haryanto (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2024)
Darmaji Village is a village located in Kopang District, Central Lombok Regency, where the village office has a central role in managing administrative affairs and community services. However, archive management in Darmaji Village still uses conventional methods that are vulnerable to the risk of damage and loss of documents. As a solution, the pengabdi took the initiative to conduct digital archive transformation training using Google Drive to help village officials manage archives more efficiently. The methods used in this service training include observation, interviews, socialization, and training. The results of this activity showed a significant increase in the ability of the participants, where the pretest results showed 88.9% of the 9 participants could not operate Google Drive as a digital archive, while the posttest results showed 100% of the participants were able to operate Google Drive properly. With the application of this technology, it is expected that archive management in Darmaji Village will become more effective, efficient, and secure, and will be able to encourage the implementation of digital technology in various aspects of village administration